Increased Vesicular Monoamine Transporter 2 (VMAT2) and Dopamine Transporter (DAT) Expression in Adolescent Brain Development: A Longitudinal Micro-PET/CT Study in Rodent - Jiang, Donglang; Lu, Xiuhong; Li, Zijing; Rydberg, Nicklas; Zuo, Chuantao; Peng, Fangyu; Hua, Fengchun; Guan, Yihui; Xie, Fang (Frontiers in Neuroscience, 2019)
Background: Brain development and maturation in adolescence is a complex process with active changes of metabolic and neurotransmission pathways. Positron emission tomography (PET) is a useful imaging modality for tracking metabolic and functional changes in adolescent brain. In this study, changes of glucose metabolism, expression of vesicular monoamine transporter 2 and dopamine transporter during adolescent brain development in rats were investigated with PET/CT . Methods: A longitudinal PET/CT study of age-dependent changes of VMAT2, DAT and glucose metabolism in adolescent brain was conducted in a group of Wistar rats (n = 6) post sequential intravenous injection of 18F-PF-(+)-DTBZ, 11C-CFT, and 18F-FDG, respectively. PET acquisition was performed at 2, 4, 9 and 12 months of age. Radiotracer uptake in different brain regions, including the striatum, cerebellum and hippocampus, were quantified and recorded as Standardized uptake value (SUV) and striatal specific uptake ratio (SUVR: SUV in striatum /SUV in cerebellum). Results: Variable uptake of 18F-PF-(+)-DTBZ and 11C-CFT were detected, with highest level uptake in the striatum and accumbens. There was significant age-dependent increase of 18F-PF-(+)-DTBZ and 11C-CFT uptake in the striatum from 2 months of age (SUV: 1.36 ± 0.22, 1.37 ± 0.39, respectively), to 4 months (SUV: 2.22 ± 0.29, 2.04 ± 0.33), 9 months (1.98 ± 0.34, 2.09 ± 0.18), 12 months (SUV: 1.93 ± 0.19, 2.00 ± 0.17) of age, SUV of 18F-FDG also increased from 2 months of age to older ages (SUV in the striatum: 3.71 ± 0.78 at 2 month, 5.28 ± 0.81, 5.14 ± 0.73, 4.94 ± 0.50 at 4, 9, 12 month, respectively). Conclusion: Age-dependent increases of striatal of 18F-FDG, 18F-PF-(+)-DTBZ and 11C-CFT uptake were detected in rats from 2 months to 4 month of age, demonstrating cerebral development presents over the first four months of age. Four months of age can be considered a safe threshold to launch brain disease studies for exclusion of confusion of continuing tissue development. These findings support further investigation of age-dependent changes in expression of DAT, VMAT2 and glucose metabolism for their potential use as a new imaging biomarker for study of brain development and functional maturation.